Multilaboratory Evaluation of a Lateral Flow Method for Aflatoxin B1 Analysis in Dry Dog Food. (20th April 2020) - Vudathala, Daljit; Klobut, Jakub; Cummings, Margie; Tkachenko, Andriy; Reimschuessel, Renate; Murphy, Lisa; ,
Abstract: Background: Aflatoxins are one of the most heavily regulated mycotoxins in agriculture throughout the world. A variety of tests are used for detection, including rapid methods that are preferred when a large number of samples need to be quickly screened to implement an immediate action. However, a method developed for screening a specific commodity for the presence of mycotoxins requires further validation to demonstrate its suitability for additional matrices. Objective: In this study, a study was undertaken to evaluate a rapid screening method for aflatoxin B1 (AFB1) in dry dog food, a product potentially susceptible to aflatoxins contamination. Method: This test method employed lateral flow technology using kits obtained from Charm Sciences Inc. Three different sources of dry dog food were tested at the FDA action level of 20 ppb (ng/g) in three trials of a multi-laboratory study by four participants. A total of 80 unfortified blank samples, 270 samples spiked at 20 ppb, and 60 samples spiked below 20 ppb were analyzed. Results: The overall pass rates of 100% for unfortified samples and > 97% for 20 ppb-fortified samples meet the FDA guidance acceptance criteria for a limit test of 10-15% false positives and no more than 5% false negatives. Conclusions: The method is suitable for screening a large number of dry dog food samples for rapid response. Highlights: Multi-laboratory evaluation of a rapid method for aflatoxin screening in dog food.